Pemanfaatan Limbah Abu Sekam dan Bonggol Jagung Sebagai Bahan Tambah dalam Proses Pembuatan Genteng Beton - Yusnika Devi Hartaji; Ahmad Rayhan; Riza Susanti; Hartono Hartono (Universitas Diponegoro, 2025)
Concrete tile has brittle properties, so it is less able to withstand loads because it has low bending strength. In addition, concrete tiles also often experience leaks caused by cracks. Therefore, innovation is needed to overcome these weaknesses. This study used materials from waste husk ash and corn weevil ash as a mixture composition. Husk ash is possible because it contains much silica, which, when combined with cement, can increase the bending strength of concrete tiles. Another material that can be used is corn weevil ash because it contains plastic properties that can fill the pores to reduce the potential for concrete tile leakage. This study used an experimental research method with a ratio of cement and sand composition of 1: 3. Substitution percentage for husk ash and corn weevil ash variation A (0% : 0%); B (7.5%: 7.5%); C (10%: 5%); D (12.5%: 2.5%). Tests were conducted based on SNI 0096-2007 for visible properties, size, flatness, flexural strength, water absorption (porosity), and water seepage (impermeability). The test results show that theoptimum concrete tile was obtained in variation C with an increase in bending strength of 24.94%, 1869.06 N, and an average water absorption of 7.91%. The production cost of concrete tiles with additional husk ash and corn weevil ash amounted to Rp 3128.82, down 0.041% due to added materials that can reduce the use of cement and sand so that production costs decrease. Based on the test results, adding husk ash and corn weevil ash gives concrete tiles higher flexural strength, more leak resistance, and more economic.